Price-earnings regressions in the presence of prices leading earnings - Kothari, S.P. (Journal of Accounting and Economics, 1992)
The paper analytically evaluates alternative specifications of price-earnings regressions when prices lead earnings, i.e., reflect information about future earnings that is not reflected in the past time series of earnings. Because prices lead earnings, the specification using the earnings-level-deflated-by-price variable in a price-earnings regression is ‘better’, in terms of bias in the estimated earnings response coefficient and explanatory power, than specifications using earnings-change-deflated-by-price and earnings-deflated-by-lagged-earnings variables. An accurate proxy for unexpected earnings, however, outperforms the earnings-level- and earnings-change-deflated-by-price specifications.